109 Feasibility and potential clinical utility of biventricular function, aortic and pulmonary flow assessment using compressed sense during continuous exercise cardiovascular magnetic resonance (EX-CMR). (17th July 2020) - Craven, Thomas; Jex, Nicholas; Higgins, David; Chew, Pei Gee; Bissell, Malenka; Brown, Louise; Saunderson, Christopher; Das, Arka; Chowdhary, Amrit; Dall'Armellina, Erica; Levelt, Eylem; Swoboda, Peter; et al.
Abstract : Background: Biventricular volume, aortic and pulmonary flow assessment by cardiovascular magnetic resonance (CMR) allows accurate direct quantification of aortic and pulmonary flow and indirect quantification of mitral and tricuspid regurgitation. Exercise cardiovascular magnetic resonance (Ex-CMR) combines the preferred method of exercise stress with the diagnostic capabilities of CMR. Compressed SENSE (CS) is a novel parallel imaging technique, robust to respiratory motion that has not previously been used in Ex-CMR. This study aims to demonstrate the feasibility and utility of performing biventricular function and flow assessment during continuous in-scanner exercise, using vendor supplied CS sequences and commercial analysis software (Circle cvi42). Methods: 12 healthy volunteers (8 male, age 35±10 years) had CMR imaging (1.5T Philips Ingenia) using a novel free breathing CS protocol at rest and during continuous in-scanner supine cycle exercise (Lode BV) to low and moderate exercise intensities. Target heart rates (THR) were individually prescribed using heart rate reserve (HRR) and an age predicted maximal heart rate model. Participants exercised with no resistance for 1 minute then at an increase of 25W every 2 minutes until target heart rate (THR) were achieved at low (30-39% HRR) and moderate (40-59% HRR) exercise. At rest, the novel CS protocol was validated against our institute's standard clinical breath-held (BH) sequences (SENSE 2, bSSFP multi-phase, multi-slice SA cines & aortic and pulmonary 2D flow). The Ex-CMR protocol involved: Biventricular volume assessment - free breathing, Compressed SENSE acceleration x 3 (CS3), bSSFP, respiratory navigated, retrospectively gated short axis cine imaging. Flow acquisition - free breathing CS3 aortic and pulmonary through-plane phase contrast imaging. Results: Resting biventricular volumes, aortic and pulmonary flows from CS3 sequences demonstrated very strong correlation with clinical breath held sequences (all correlations r >0.93, p<0.01). Participant's heart rates remained within the prescribed exercise intensities for each stage (table 1 ). Examples of exercise image quality are presented in figure 1 . Biventricular end-diastolic volumes (EDV) remained unchanged with increasing exercise (with the exception of a drop in right ventricular EDV at moderate exercise), with an increase in stroke volumes (SV) driven by a fall in end systolic volumes (table 2 ). Aortic and pulmonary stroke volumes similarly rose with increasing exercise intensities, strongly correlating at all exercise intensities with the corresponding stroke volumes acquired from biventricular SA cine imaging (all correlations: r >0.88, p <0.01). Conclusion: This is the first study to demonstrate feasibility of biventricular function, aortic and pulmonary flow assessment during continuous Ex-CMR using vendor provided sequences and commercially available analysis software. The developed Compressed SENSE Ex-CMR protocol could easily be adopted across a wide number of centres, potentially allowing assessment of the haemodynamic response to a wide range of cardiovascular diseases, therefore increasing the clinical utility of Ex-CMR. Conflict of Interest: N/A